1995
DOI: 10.1095/biolreprod52.4.848
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Bovine Uterine Proteins in Response to Type I Interferons1

Abstract: Bovine interferon-tau (bIFN-tau) is secreted by the developing conceptus and initiates antiluteolytic events by interacting with uterine membrane receptors. We have identified three endometrial proteins (approximately 8, 16, and 28 kDa; P8, P16, and P28; respectively) that are secreted in response to recombinant (r) bIFN-tau. The objective of this study was to determine whether or not secretion of these proteins was a unique response to IFN-tau during early pregnancy. Three experiments were designed to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…The appearance of anti-UCRP immunoreactivity in decidual cells at the beginning of pregnancy indicates that it may play an important role in the establishment of the conceptus. An anti-UCRP-immunoreactive polypeptide of 16 kDa, which appears to be free UCRP [13], is found in uterine washes of pregnant, but not nonpregnant, cows and is one of a small number of proteins released from the endometrium in response to IFN [21], which suggests that the protein is specifically secreted from uterine tissue. The functional significance of these findings is not clear, although the secretion of IFN-␥ by monocytes in response to UCRP has previously been reported [37] and the protein therefore may play a vital role in coordination of the complex network of IFNs during the initiation of bovine pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of anti-UCRP immunoreactivity in decidual cells at the beginning of pregnancy indicates that it may play an important role in the establishment of the conceptus. An anti-UCRP-immunoreactive polypeptide of 16 kDa, which appears to be free UCRP [13], is found in uterine washes of pregnant, but not nonpregnant, cows and is one of a small number of proteins released from the endometrium in response to IFN [21], which suggests that the protein is specifically secreted from uterine tissue. The functional significance of these findings is not clear, although the secretion of IFN-␥ by monocytes in response to UCRP has previously been reported [37] and the protein therefore may play a vital role in coordination of the complex network of IFNs during the initiation of bovine pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible, therefore, that the ubiquitin system could be involved in the extensive uterine remodeling during the menstrual cycle and pregnancy. Recent work by Hansen and coworkers has shown that UCRP is one of the proteins secreted by the bovine uterus in response to type 1 interferons [21]. The bovine conceptus produces IFNduring the first 30 days of pregnancy prior to placental attachment, during which time it is thought to maintain the pregnant state [22].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of IRF-1 protein was evident at 1 h after IFN-treatment in BEND cells [23]. The IFNinduced gene transcription in bovine and ovine uteri [47][48][49][50][51]. One product of IFN--induced transcription is ISG17 [52].…”
Section: Discussionmentioning
confidence: 99%
“…Such findings do not dismiss the possibility that IFN-ô contains a unique ability to act on other aspects of pregnancy recognition, such as modulating the local immune system or controlling uterine protein production. In fact, uterine secretions are slightly different following treatment with IFN-ô and IFN-á (Naivar et al, 1995). The production of at least one uterine protein, granulocyte chemotactic protein-2, is stimulated by IFN-ô but not by IFN-á in bovine endometrium (Staggs et al, 1998).…”
Section: Is Ifn-ô Unique Among Ifns For Serving As the Mrp Signal?mentioning
confidence: 95%